Analytical methods for meldonium determination in urine samples. (22nd January 2021) - Rusu, L. D.; Bratu, I.; Măruțoiu, C.; Moldovan, Z.; Rada, M.
Abstract: Here is reported a rapid analytical method for meldonium and other beta blockers (metoprolol, amlodipine, bisoprolol, nebivolol, betaxolol, and carvediol) in urine samples using Fourier transform infrared spectroscopy (FTIR) for the detection of these forbidden compounds in athletes. A thin layer chromatography (TLC) plate coated with SiO2 was employed. Simple analytical methods for screening meldonium and the aforementioned beta blockers in urine samples were developed using the TLC plates, FTIR spectroscopy with the aid of KBr pellet technique, and mass spectrometry. The surface hydroxyl groups were employed for the indirect detection of meldonium in the urine samples. The detection and quantification of meldonium were also confirmed by mass spectrometry by the use of both electron impact (EI) and electrospray (ESP) ionization systems.